Pentingnya Peran Orangtua Dalam Mendampingi Anak Usia Dini di Awal Era New Normal - Amelia Putri Nirmala (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2021)
The family is the best madrasa for early childhood. At this time, early childhood enters the golden age, a very appropriate time to teach all good behavior, teach social norms because what parents exemplify will indirectly shape the child's personality. The situation in Indonesia after the Covid pandemic has put all levels of society, including early childhood, in a new situation, namely the new normal. New normal: a new situation to get used to complying with health protocols in all activities. Health protocols must be applied in everyday life. The purpose of this study was to determine the role of parents in assisting early childhood at the beginning of the new normal era. The research used is a qualitative approach with a descriptive type. In addition, researchers used the observation method to observe the activities of parents and children in their daily lives. The results of the research that has been done are that the role of parents is very important in implementing new habits, parents play an important role in guiding, assisting early childhood learning and playing. Parents play an important role in providing comfort, creative games so that early childhood does not feel bored and bored when doing activities at home during the new normal era.